Hydrogenated nitrile rubber as well as preparation method and application thereof
通过制备高比重的氢化丁腈橡胶,解决了氟橡胶材料因比重低和欧洲化学品管理局限制的问题,实现了其在智能穿戴设备中的高效替代应用。
Patent Information
- Application Number
- CN202411769592.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
AI Technical Summary
Due to the restrictions of the European Chemicals Agency and its proportion is low, it is difficult to meet the high proportion demand for smart wearable devices.
By preparing a hydrogenated nitrile rubber, its preparation raw materials include hydrogenated acrylonitrile-butadiene copolymer, inorganic metal compounds, etc., the specific gravity and performance are improved by plasticizing, intensive refining, refining and vulcanizing molding.
The obtained hydrogenated nitrile rubber has high specific gravity, chemical resistance and aging resistance. Its performance is comparable to fluoroelastic materials and can replace the application of fluoroelastic in smart wearable devices.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a hydrogenated nitrile rubber and a preparation method and application thereof. Background Art
[0002] Fluororubber is widely used in smart wearable products due to its high specific gravity, good chemical resistance and aging resistance. However, with the announcement of the European Chemicals Agency (ECHA)'s proposal to ban the production and use of perfluorinated and polyfluoroalkyl compounds (PFAS), the use of fluororubber has been restricted; at the same time, with the increasing popularity of smart wearable products, it is a development trend to provide a rubber material that can replace fluororubber for use in smart wearable devices. Hydrogenated nitrile rubber (HNBR) is a highly saturated special elastomer made by selectively hydrogenating the unsaturated carbon-carbon double bonds in the main chain of nitrile rubber (NBR) molecules; HNBR inherits the original excellent oil resistance of NBR, and also has the characteristics of chemical resistance and aging resistance; however, compared with the fluororubber materials used in smart wearable products in the prior art, the specific gravity of hydrogenated nitrile rubber is lower.
[0003] Therefore, it is very necessary to provide a hydrogenated nitrile rubber that can replace fluororubber and be used in the manufacture of smart wearable devices. Summary of the invention
[0004] The purpose of the present invention is to solve the above problems and provide a hydrogenated nitrile rubber and a preparation method and application thereof. The hydrogenated nitrile rubber has good chemical resistance and aging resistance and high specific gravity, and can replace fluororubber materials and be applied to smart wearable devices.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:
[0006] In a first aspect, the present invention provides a hydrogenated nitrile rubber, wherein the raw materials for preparing the hydrogenated nitrile rubber include, by mass percentage, 34%-45% of hydrogenated acrylonitrile-butadiene copolymer, 0.2%-0.5% of processing aid, 0.5%-1% of filler, 45%-55% of inorganic metal compound, 0.5%-0.7% of silane coupling agent, 0.3%-0.5% of antioxidant, 0.01%-0.03% of UV agent, 2%-5% of plasticizer, 0.5%-1% of cross-linking aid and 1.5%-2.5% of vulcanizing agent; wherein the inorganic metal compound includes at least one of barium sulfate, barium titanate, zirconium oxide, zirconium carbide, tungsten carbide, aluminum hydroxide, calcium fluoride and ammonium chloride.
[0007] Optionally, the hydrogenated acrylonitrile-butadiene copolymer includes a hydrogenated acrylonitrile-butadiene copolymer with a grade of DN1818, DN2118, DN3408, DN3418, DN4308 or DN4309 produced by Dawn Group, or a hydrogenated acrylonitrile-butadiene copolymer with a grade of ZN28255, ZN35056 or ZN35158 produced by Zannan Technology (Shanghai) Co., Ltd., or a hydrogenated acrylonitrile-butadiene copolymer with a grade of HNBR3605 produced by Sinopec, or a hydrogenated acrylonitrile-butadiene copolymer with a grade of NBR3330C, NBR337 ... 3445F, 3470F, 3945F, 3965F, At least one of the hydrogenated acrylonitrile-butadiene copolymers of 3330F.
[0008] Optionally, the silane coupling agent includes one or both of silane coupling agent A-171 or silane coupling agent A-172; silane coupling agent A-171 (vinyl trimethoxysilane), whose molecular formula is CH2=CHSi(OCH3)3; silane coupling agent A-172 (vinyl triethoxysilane), whose molecular formula is CH2=CHSi(OC2H5)3. The antioxidant includes triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate]; the UV agent includes ultraviolet absorber UV-P; the plasticizer includes trioctyl trimellitate; the crosslinking aid includes trimethylolpropane trimethacrylate; and the vulcanizing agent includes dipentadienol.
[0009] Optionally, the filler includes one or more of fumed silica, carbon black, conductive carbon black or white carbon black. In some embodiments, the filler is fumed silica, which, as a high-performance filler, can significantly improve the mechanical properties, processing properties, heat resistance and aging resistance of rubber materials, while improving the surface quality and electrical insulation properties.
[0010] In a second aspect, the present invention provides a method for preparing a hydrogenated nitrile rubber, which is used to prepare the hydrogenated nitrile rubber as described above, comprising the steps of:
[0011] S1, plasticizing: plasticizing the hydrogenated acrylonitrile-butadiene copolymer at a first temperature to obtain a plasticizing system;
[0012] S2, banburying: adding processing aids, fillers, inorganic metal compounds, silane coupling agents, antioxidants, UV agents, plasticizers, crosslinking aids and vulcanizing agents to the plasticized system obtained in step S1, and banburying at a second temperature to obtain a banburying system; wherein the inorganic metal compound comprises at least one of barium sulfate, barium titanate, zirconium oxide, zirconium carbide, tungsten carbide, aluminum hydroxide, calcium fluoride and ammonium chloride; during the banburying process of step S2, the raw materials other than the polyether type mixed polyurethane rubber are added together for banburying, without adding in batches, thereby improving the preparation efficiency and reducing the power energy consumption of production;
[0013] S3, refining: refining the internal mixing system obtained in step S2 at a third temperature to obtain a mixed rubber material;
[0014] S4, molding: After cooling the mixed rubber obtained in step S3 to 25-40° C., vulcanization molding is performed to obtain hydrogenated nitrile rubber.
[0015] Optionally, the raw materials for preparing the hydrogenated nitrile rubber include, by mass percentage, 34%-45% of hydrogenated acrylonitrile-butadiene copolymer (HNBR), 0.2%-0.5% of a processing aid, 0.5%-1% of a filler, 45%-55% of an inorganic metal compound, 0.5%-0.7% of a silane coupling agent, 0.3%-0.5% of an antioxidant, 0.01%-0.03% of a UV agent, 2%-5% of a plasticizer, 0.5%-1% of a cross-linking aid and 1.5%-2.5% of a vulcanizing agent.
[0016] Optionally, the first temperature is 25-100°C, and the plasticating time is 3-5 minutes; the second temperature is 25-100°C, and the mixing time is 10-15 minutes, and the glue outlet temperature is 100°C; the third temperature is 25-70°C, and the refining time is 10-15 minutes.
[0017] Optionally, in step S4, the molding is carried out at a temperature of 172±5°C and a pressure of 180-200kg, and the molding time is 200-300s.
[0018] In a third aspect, the present invention provides an application of the hydrogenated nitrile rubber as described above in a smart wearable device. For example, the hydrogenated nitrile rubber can be used to prepare smart devices such as VR glasses, smart watch straps, and smart headphones.
[0019] The beneficial effects produced by the present invention include at least:
[0020] The present invention provides a hydrogenated nitrile rubber for use in replacing fluororubber in the preparation of wearable devices. No fluorine is added to the preparation raw materials, and an inorganic metal compound with a high specific gravity is added to increase the specific gravity of the obtained hydrogenated nitrile rubber, so that the hydrogenated nitrile rubber obtained by the present invention has the characteristics of chemical resistance and aging resistance while having a high specific gravity characteristic, and the performance is comparable to that of fluororubber materials, and can replace fluororubber materials in the preparation of products such as smart wearable devices. DETAILED DESCRIPTION
[0021] In order to facilitate the understanding of the present invention, the preferred embodiments of the present invention are provided below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described in the present invention. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0022] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0023] It should be noted that, unless otherwise specified, the raw materials used in the present invention can be sourced from suppliers known in the art or prepared by known methods.
[0024] In a first aspect, the present invention provides a hydrogenated nitrile rubber, wherein the raw materials for preparing the hydrogenated nitrile rubber include, by mass percentage, 34%-45% of hydrogenated acrylonitrile-butadiene copolymer (HNBR), 0.2%-0.5% of a processing aid, 0.5%-1% of a filler, 45%-55% of an inorganic metal compound, 0.5%-0.7% of a silane coupling agent, 0.3%-0.5% of an antioxidant, 0.01%-0.03% of a UV agent, 2%-5% of a plasticizer, 0.5%-1% of a cross-linking aid, and 1.5%-2.5% of a vulcanizing agent; wherein the inorganic metal compound includes at least one of barium sulfate, barium titanate, zirconium oxide, zirconium carbide, tungsten carbide, aluminum hydroxide, calcium fluoride, and ammonium chloride.
[0025] The present invention provides a hydrogenated nitrile rubber for use in replacing fluororubber in the preparation of wearable devices. No fluorine is added to the preparation raw materials, and an inorganic metal compound with a high specific gravity is added to increase the specific gravity of the obtained hydrogenated nitrile rubber, so that the hydrogenated nitrile rubber obtained by the present invention has the characteristics of chemical resistance and aging resistance while having a high specific gravity characteristic, and the performance is comparable to that of fluororubber materials, and can replace fluororubber materials in the preparation of products such as smart wearable devices.
[0026] Optionally, the hydrogenated acrylonitrile-butadiene copolymer includes a hydrogenated acrylonitrile-butadiene copolymer with a grade of DN1818, DN2118, DN3408, DN3418, DN4308 or DN4309 produced by Dawn Group, or a hydrogenated acrylonitrile-butadiene copolymer with a grade of ZN28255, ZN35056 or ZN35158 produced by Zannan Technology (Shanghai) Co., Ltd., or a hydrogenated acrylonitrile-butadiene copolymer with a grade of HNBR3605 produced by Sinopec, or a hydrogenated acrylonitrile-butadiene copolymer with a grade of NBR3330C, NBR337 ... 3445F, 3470F, 3945F, 3965F, In some embodiments, the hydrogenated acrylonitrile-butadiene copolymer can be selected from a combination of hydrogenated acrylonitrile-butadiene copolymers with medium, high and low Mooney viscosities to form a hydrogenated nitrile rubber mixed system with different Mooney viscosities. For example, a hydrogenated nitrile rubber mixed system composed of DN3418, DN4308 and DN4309 produced by Dawn Group is used.
[0027] The hydrogenated nitrile rubber of the present invention uses domestic hydrogenated nitrile raw rubber, which reduces the production cost of the hydrogenated nitrile rubber material, effectively reduces the dependence on imported materials, and ensures the continuity and stability of the production process.
[0028] Optionally, the silane coupling agent includes one or both of silane coupling agent A-171 or silane coupling agent A-172; silane coupling agent A-171 (vinyltrimethoxysilane), whose molecular formula is CH2=CHSi(OCH3)3; silane coupling agent A-172 (vinyltriethoxysilane), whose molecular formula is CH2=CHSi(OC2H5)3.
[0029] Optionally, the antioxidant includes triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate]; the UV agent includes ultraviolet absorber UV-P; the plasticizer includes trioctyl trimellitate; the cross-linking aid includes trimethylolpropane trimethacrylate; and the vulcanizing agent includes dipentadienyl.
[0030] Among them, in the present invention, trioctyl trimellitate is used as a plasticizer to improve the flexibility, ductility, processing performance, aging resistance, chemical resistance, electrical insulation performance, surface finish and low temperature performance of the hydrogenated nitrile rubber material.
[0031] Optionally, the filler includes one or more of fumed silica, carbon black, conductive carbon black or white carbon black. In some embodiments, the filler is fumed silica, which, as a high-performance filler, can significantly improve the mechanical properties, processing properties, heat resistance and aging resistance of rubber materials, while improving the surface quality and electrical insulation properties.
[0032] In a second aspect, the present invention provides a method for preparing a hydrogenated nitrile rubber, which is used to prepare the hydrogenated nitrile rubber as described above, comprising the steps of:
[0033] S1, plasticizing: plasticizing the hydrogenated acrylonitrile-butadiene copolymer (HNBR) at a first temperature to obtain a plasticizing system;
[0034] S2, banburying: adding processing aids, fillers, inorganic metal compounds, silane coupling agents, antioxidants, UV agents, plasticizers, crosslinking aids and vulcanizing agents to the plasticized system obtained in step S1, and banburying at a second temperature to obtain a banburying system; wherein the inorganic metal compound comprises at least one of barium sulfate, barium titanate, zirconium oxide, zirconium carbide, tungsten carbide, aluminum hydroxide, calcium fluoride and ammonium chloride; during the banburying process of step S2, the raw materials other than the polyether type mixed polyurethane rubber are added together for banburying, without adding in batches, thereby improving the preparation efficiency and reducing the power energy consumption of production;
[0035] S3, refining: refining the internal mixing system obtained in step S2 at a third temperature to obtain a mixed rubber material;
[0036] S4, molding: After cooling the mixed rubber obtained in step S3 to 25-40° C., vulcanization molding is performed to obtain hydrogenated nitrile rubber.
[0037] Optionally, the raw materials for preparing the hydrogenated nitrile rubber include, by mass percentage, 34%-45% of hydrogenated acrylonitrile-butadiene copolymer (HNBR), 0.2%-0.5% of a processing aid, 0.5%-1% of a filler, 45%-55% of an inorganic metal compound, 0.5%-0.7% of a silane coupling agent, 0.3%-0.5% of an antioxidant, 0.01%-0.03% of a UV agent, 2%-5% of a plasticizer, 0.5%-1% of a cross-linking aid and 1.5%-2.5% of a vulcanizing agent. The preparation method described in the present invention provides a hydrogenated nitrile rubber for replacing fluororubber in the preparation of wearable devices. No fluorine is added to the preparation raw materials, and an inorganic metal compound with a high specific gravity is added to increase the specific gravity of the obtained hydrogenated nitrile rubber, so that the hydrogenated nitrile rubber obtained in the present invention has the characteristics of chemical resistance and aging resistance while also having the characteristics of high specific gravity. The performance is comparable to that of fluororubber materials, and can replace fluororubber materials in the preparation of products such as smart wearable devices.
[0038] Specifically, the addition amount of the hydrogenated acrylonitrile-butadiene copolymer (HNBR) may be 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44% or 45%; the addition amount of the processing aid may be 0.2%, 0.3%, 0.4% or 0.5%; the addition amount of the filler may be 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; the addition amount of the inorganic metal compound may be 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100%, 101%, 102%, 103%, 104%, 105%, 106%, 107%, 108%, 109%, 110%, 111%, 112%, 113%, 114%, 115%, 116%, 117%, 118%, 119%, 120%, 121%, 122%, 123%, 124%, 125%, 126 2%, 53%, 54% or 55%; the addition amount of the silane coupling agent is 0.5%, 0.6% or 0.7%; the addition amount of the antioxidant is 0.3%, 0.4% or 0.5%; the addition amount of the UV agent can be 0.01%, 0.02% or 0.03%; the addition amount of the plasticizer can be 2%, 3%, 4% or 5%; the addition amount of the cross-linking aid can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%; the addition amount of the vulcanizing agent can be 1.5%, 2.0% or 2.5%.
[0039] Optionally, the first temperature is 25-100°C, and the plasticizing time is 3-5 minutes; based on the comprehensive consideration of the performance of the high-density polyurethane rubber to be prepared and the power energy consumption, the present invention preferably sets the plasticizing time to 3-5 minutes, and within the preferred plasticizing time range, the effects of improving the plasticity of the rubber system, reducing elasticity, reducing viscosity, improving fluidity, and improving the solubility and molding adhesion of the rubber are achieved; at the same time, the power consumption of production is avoided to the greatest extent. The second temperature is 25-100°C, the mixing time is 10-15 minutes, and the glue outlet temperature is 100°C; the third temperature is 25-70°C, and the refining time is 10-15 minutes.
[0040] Optionally, in step S4, the molding is carried out at a temperature of 172±5°C and a pressure of 180-200kg, and the molding time is 200-300s.
[0041] In a third aspect, the present invention provides an application of the hydrogenated nitrile rubber as described above in a smart wearable device. For example, the hydrogenated nitrile rubber can be used to prepare smart devices such as VR glasses, smart watch straps, and smart headphones.
[0042] Example:
[0043] The hydrogenated nitrile rubber is prepared by the above-mentioned preparation method, which comprises the steps of:
[0044] S1, plasticizing: plasticizing the hydrogenated acrylonitrile-butadiene copolymer at a first temperature to obtain a plasticizing system; the first temperature is 25-100° C., and the plasticizing time is 3-5 min; the hydrogenated acrylonitrile-butadiene polymer used in the embodiment of the present application is a hydrogenated nitrile raw rubber mixed system composed of DN3418, DN4308 and DN4309 produced by Dawn Group;
[0045] S2, banburying: adding processing aid, filler, inorganic metal compound, silane coupling agent, antioxidant, UV agent, plasticizer, crosslinking aid and vulcanizing agent to the plasticized system obtained in step S1, and banburying at a second temperature to obtain a banburying system; wherein the inorganic metal compound is barium titanate; the second temperature is 25-100°C, the banburying time is 10-15min, and the discharging temperature is 100°C.
[0046] S3, refining: refining the internal mixing system obtained in step S2 at a third temperature to obtain a mixed rubber material; the third temperature is 25-75° C., and the refining time is 10-15 minutes.
[0047] S4, molding: After the mixed rubber obtained in step S3 is cooled to 25-40° C., vulcanization molding is performed to obtain hydrogenated nitrile rubber. The molding is performed at a temperature of 172±5° C. and a pressure of 180-200 kg, and the molding time is 200-300 seconds, preferably 300 seconds.
[0048] In the step S4 molding process, a rotorless vulcanizer is used to test the vulcanization curve at 170±3°C, and the test data are recorded as follows: T10 (i.e., scorch time) is 20-35s, and T90 (i.e., process positive vulcanization time) is 80-120s. It can be seen from the vulcanization curve that the vulcanization time obtained by the preparation method of the high specific gravity polyurethane rubber of the present invention is short and easy to mold, thereby ensuring the stability of the molding of the polyurethane rubber; and further ensuring that the polyurethane rubber obtained after molding has good hardness, tensile resistance and elongation.
[0049] The polyurethane rubber prepared in Example 1 was tested for hardness (Shore A), specific gravity, tensile strength, elongation and Mooney viscosity. The test methods are as follows: the hardness test was measured using a type A Shore durometer, and the reference standard was GB / T531 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber"; the tensile strength and elongation tests were performed using a universal tensile testing machine, and the reference standard was GB / T528 "Determination standard for tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; the Mooney viscosity test condition was ML (1+4, 100°C), and the reference standard was GB / T 1232.1-2000. After testing, the various properties of the hydrogenated nitrile rubber prepared by the preparation method described above were: hardness (Shore A) was 65-75A, average specific gravity was 1.95g / cm, tensile strength was 12-15MPA, elongation was 300-450%, and Mooney viscosity was 80-90MU. The performance parameters of fluororubber materials used in smart wearable devices in the prior art are generally: hardness (Shore A) of 70±5A, average specific gravity of 1.95±0.2g / cm, tensile strength of greater than 12MPA, and elongation of greater than 200%. This shows that the high specific gravity polyurethane resin obtained by the present invention can replace fluororubber materials and be used in smart wearable devices.
[0050] The technical features of the above embodiments may be combined arbitrarily. To make the description concise, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0051] The above embodiments only express the preferred implementation modes of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A hydrogenated nitrile rubber, characterized in that: The raw materials for preparing the hydrogenated nitrile rubber include 34%-45% of hydrogenated acrylonitrile-butadiene copolymer, 0.2%-0.5% of processing aid, 0.5%-1% of filler, 45%-55% of inorganic metal compound, 0.5%-0.7% of silane coupling agent, 0.3%-0.5% of antioxidant, 0.01%-0.03% of UV agent, 2%-5% of plasticizer, 0.5%-1% of cross-linking aid and 1.5%-2.5% of vulcanizing agent; wherein the inorganic metal compound includes at least one of barium sulfate, barium titanate, zirconium oxide, zirconium carbide, tungsten carbide, aluminum hydroxide, calcium fluoride and ammonium chloride.
2. The hydrogenated nitrile rubber according to claim 1, wherein: The hydrogenated acrylonitrile-butadiene copolymer includes the hydrogenated acrylonitrile-butadiene copolymer with the brand DN1818, DN2118, DN3408, DN3418, DN4308 or DN4309 produced by Dawn Group, or the hydrogenated acrylonitrile-butadiene copolymer with the brand ZN28255, ZN35056 or ZN35158 produced by Zannan Technology (Shanghai) Co., Ltd., or the hydrogenated acrylonitrile-butadiene copolymer with the brand HNBR3605 produced by Sinopec, or the hydrogenated acrylonitrile-butadiene copolymer with the brand NBR3330C, NBR3370C, At least one of the hydrogenated acrylonitrile-butadiene copolymers.
3. The hydrogenated nitrile rubber according to claim 1, characterized in that: The silane coupling agent includes one or both of silane coupling agent A-171 and silane coupling agent A-172; the antioxidant includes triethylene glycol bis[β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate]; the UV agent includes ultraviolet absorber UV-P; the plasticizer includes trioctyl trimellitate; the cross-linking aid includes trimethylolpropane trimethacrylate; and the vulcanizing agent includes dipentadienyl propionate.
4. The hydrogenated nitrile rubber according to claim 1, characterized in that: The filler includes one or more of fumed silica, carbon black, conductive carbon black or white carbon black.
5. A method for preparing hydrogenated nitrile rubber, characterized in that: For preparing the hydrogenated nitrile rubber as claimed in any one of claims 1 to 4, comprising the steps of: S1, plasticizing: plasticizing the hydrogenated acrylonitrile-butadiene copolymer at a first temperature to obtain a plasticizing system; S2, banburying: adding processing aids, fillers, inorganic metal compounds, silane coupling agents, antioxidants, UV agents, plasticizers, crosslinking aids and vulcanizing agents to the plasticized system obtained in step S1, and banburying at a second temperature to obtain a banburying system; wherein the inorganic metal compound comprises at least one of barium sulfate, barium titanate, zirconium oxide, zirconium carbide, tungsten carbide, aluminum hydroxide, calcium fluoride and ammonium chloride; during the banburying process of step S2, the raw materials other than the polyether type mixed polyurethane rubber are added together for banburying, without adding in batches, thereby improving the preparation efficiency and reducing the power energy consumption of production; S3, refining: refining the internal mixing system obtained in step S2 at a third temperature to obtain a mixed rubber material; S4, molding: After cooling the mixed rubber obtained in step S3 to 25-40° C., vulcanization molding is performed to obtain hydrogenated nitrile rubber.
6. The method for preparing hydrogenated nitrile rubber according to claim 5, wherein: Measured in mass percentage, the raw materials for preparing the hydrogenated nitrile rubber include 34%-45% of hydrogenated acrylonitrile-butadiene copolymer, 0.2%-0.5% of processing aid, 0.5%-1% of filler, 45%-55% of inorganic metal compound, 0.5%-0.7% of silane coupling agent, 0.3%-0.5% of antioxidant, 0.01%-0.03% of UV agent, 2%-5% of plasticizer, 0.5%-1% of cross-linking aid and 1.5%-2.5% of vulcanizing agent.
7. The method for preparing hydrogenated nitrile rubber according to claim 5, wherein: The first temperature is 25-100°C, and the plasticating time is 3-5 minutes; the second temperature is 25-100°C, and the banburying time is 10-15 minutes, and the glue outlet temperature is 100°C; the third temperature is 25-70°C, and the refining time is 10-15 minutes.
8. The method for preparing hydrogenated nitrile rubber according to claim 5, wherein: In step S4, the molding is carried out at a temperature of 172±5° C. and a pressure of 180-200 kg, and the molding time is 200-300 seconds.
9. Use of the hydrogenated nitrile rubber as described in any one of claims 1 to 4 in an intelligent wearable device.